LINGUISTIC PICTURE OF THE WORLD IN THE FORMATION OF AN INDIVIDUAL’S ETHNIC IDENTITY - Корнієнко, Людмила (SWorldJournal, 2024)
The article analyzes the role and the meaning of a language in the formation of the ethnic identity of the individual. The phenomenon of the language is considered through the prism of concepts of information. The language is stated to be the most univers